A Comparative Study of Online Media for Arabic Teaching in Indonesia - Siti Maesaroh; Viqie Ixbal Maulana; Afiyah (State Islamic University (UIN) of Sunan Ampel Surabaya, Indonesia, 2022)
This study aims to compare the electronic educational facilities used in this era with the spread of COVID-19 around the world. This study uses a comparative descriptive with a qualitative approach. Therefore, all teachers and students must take advantage of the learning process via the internet or electronic means, such as Zoom, Google Meet, Skype, Facebook, WhatsApp, Instagram, and so on. Each has advantages and disadvantages. For example, when we use Zoom and Google, we can call 100 people now, but we need stronger internet, but if we use WhatsApp, we can connect even to weaker internet, but we only call eight people. As for Skype, it is not unusual. As for Facebook and Instagram, most of their use is on social media, but we can create groups in it, like on WhatsApp, so we can send materials and work there, and we can see whenever we want. None of the above electronic means is better than the other because each has advantages and disadvantages.